Death not life, or, The destruction of the wicked (commonly called annihilation) established and endless misery disproved by a collection and explanation of all passages on future punishment : to which is added a review of Dr. E. Beecher's Conflict of ages and John Foster's letter / by Jacob Blain. - Blain, Jacob. (Tufts University. Tisch Library., 2015)
Eighth edition.; 1 online resource (117, 41, 8 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.